Effect of tool transverse speed and pin offset on the properties of friction stir welding Al6061-St52 dissimilar joint - Mehrshad Alimadadi; Mahdi Mahmoudiniya; Massoud Goodarzi; S.M.A. Boutorabi (Journal of Advanced Joining Processes, 2022)
The present study aimed to create an Al6061-St52 dissimilar joint and investigate the effect of the transverse speed and the pin offset by the friction stir welding (FSW) process. Aluminum to steel dissimilar welding is difficult by fusion methods because of the formation of brittle intermetallic compounds (IMCs). Therefore, FSW parameters were determined to designate optimal IMC thickness and acceptable mechanical properties. This research was carried out at different transverse speeds of 16, 25, 40, 55, 70, and 85 mm/min (with a constant pin offset of 0.2 mm), and various offsets of 0.8 mm, 0.4 mm, and 0 mm (with a constant transverse speed of 85 mm/min). During the study of the transverse speed parameter, the highest ultimate tensile strength (UTS) of 200 MPa was obtained at 85 mm/min, while during the investigation of the offset parameter, the highest UTS of 175 MPa was achieved in the offset of 0.4 mm. According to the Energy Dispersive X-ray Spectroscopy results, an IMC layer formed in the joint interface. The heat input rate was calculated to designate the optimal parameters. In tensile specimens, fracture mainly occurred in the joints and within the aluminum stir zone due to the combination of thick IMC layer and steel fragments, respectively. Because of the presence of different microstructures, various hardness values were observed in the weld zone. The micro-hardness measurement showed that at the transverse speed of 85 mm/min the hardness values were 75 HV in the aluminum stir zone and 315 HV in the AS vicinity of the interface region. This hardness value was much higher than the base metals (Aluminum base metal is an average of 53 HV and an average steel base metal of 245 HV).